Transición energética en Francia para la incorporación de fuentes de energías no convencionales y redes inteligentes (2019)
Despite the fact that the installed capacity in nuclear energy in the French electricity market still represents the highest percentage, 47% in 2017, non-conventional renewable energies resources, wind and solar, already represent 17% of the total installed capacity; however, in terms of generation, 70% remains nuclear. Furthermore, this market is one of the few in the European Union that has implemented a reliability mechanism and where the tariff for the provision of electricity service promotes a demand response program based on critical peak prices, in order to guarantee the reliability of supply. It is therefore important to know the energy transformation program launched in 2015 in France in order to promote green growth, reduce greenhouse emissions and strengthen energy independence; moreover, what has been done to implement smart grids in this market, which is the aim of this paper.